A framing analysis on the portrayal of Filipino two-time champion Carlos Yulo by mainstream online news outlets from 2018 to 2024 - Limpiada, Jairus B.
Carlos Yulo’s “golden moment” after bagging two gold medals in the 2024 Paris Olympics became short-lived after news broke out of his feud with his mother in the following days of his win, eventually shifting the attention away from his triumph and shining a bad light on the athlete’s name. This study aims to discover the trend in portrayal of the Filipino gymnast from 2018 to 2024 in the stories published by mainstream online news organizations to address the research gap in the shifting behaviors of news frames and representations in sports stories. Guided by de Vreese’s (2005) framing process and Hall’s (1997) representations theory, the researcher developed a coding sheet capable of measuring news frames and representations within Yulo-related stories, followed by a set of interviews with the sports editors of the online news outlets to determine the newsroom culture within their organization. Results showed that the portrayal of Yulo throughout the years was not only influenced by the core values of the online news organizations but was also determined by the athlete’s success in international competitions, signaling sports media’s high regard for the matter and influence in their framing and representations of a news subject.